AN ANALYSIS ON AFFIXES USED IN JOE BIDEN’S SPEECH - Salsabillah Nurulhaq Baderan; Ignatius J. C Tuerah; Sanerita T. Olii (Program Studi Pendidikan Bahasa Inggris, 2023)
This study focuses on identifying the most common types of affixes that younger people learning new words encounter. Its purpose is to assist students at this level in better understanding the words they come across. It has been determined that only a relatively small number of prefixes and suffixes are worth teaching in intermediate-level courses. The research process involved gathering data from library databases and online journals to decide on the research objectives, research objects, data sources, data collection methods, and data analysis. The main emphasis of this study is on suffix affixes directly extracted from Joe Biden's speech, with included data extracts to enhance the research findings. The analysis of the speech revealed that the prefix